2022
DOI: 10.1097/yic.0000000000000448
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and metabolic syndrome in patients treated with long-acting injectables antipsychotics: a retrospective study

Abstract: The present cross-sectional, retrospective study aimed to assess the prevalence of cardiovascular disease (CVD) risk factors and metabolic syndrome in a sample of psychiatric patients treated with long-acting injectable antipsychotics (LAIs). The clinical charts of 120 patients, mainly diagnosed with schizophrenia (30.0%), schizoaffective disorder (15.0%), and bipolar disorder (13.3%) on LAIs therapy -initiated in the period from 2013 to 2019 and lasting at least one year -were retrospectively reviewed and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Long-term psychopharmacotherapy may aggravate the already heightened susceptibility to cardiometabolic diseases in psychiatric patients. In line with this, we have also recently discussed the consequences of psychopharmacology on cardiovascular disease risk factors, including metabolic syndrome, hyperglycemia, and obesity (De Carlo et al, 2023;Osimo et al, 2023). These conditions, notably higher BMI and type 2 diabetes, are also implicated in specific psychiatric challenges -chronicity, treatment resistance, and symptom severity -further necessitating a nuanced approach in clinical decisions and psychopharmacological prescribing (Fanelli and Serretti, 2022;Kraus et al, 2023;Possidente et al, 2023).…”
mentioning
confidence: 90%
“…Long-term psychopharmacotherapy may aggravate the already heightened susceptibility to cardiometabolic diseases in psychiatric patients. In line with this, we have also recently discussed the consequences of psychopharmacology on cardiovascular disease risk factors, including metabolic syndrome, hyperglycemia, and obesity (De Carlo et al, 2023;Osimo et al, 2023). These conditions, notably higher BMI and type 2 diabetes, are also implicated in specific psychiatric challenges -chronicity, treatment resistance, and symptom severity -further necessitating a nuanced approach in clinical decisions and psychopharmacological prescribing (Fanelli and Serretti, 2022;Kraus et al, 2023;Possidente et al, 2023).…”
mentioning
confidence: 90%
“…In particular, the newer antipsychotics, although better tolerated than previous generations of drugs, have a high incidence rate of metabolic syndrome. This topic has already been extensively studied, including in this journal (Ijaz et al ., 2018; Akinola et al ., 2023; De Carlo et al ., 2023; Osimo et al ., 2023). The article in this issue presents data that further contributes to our understanding of the phenomenon, not least because it uses a strict definition of metabolic syndrome (Abdel Aziz et al ., 2024).…”
mentioning
confidence: 99%
“…Cardiometabolic disorders including metabolic syndrome are up to five times as common in people with chronic psychotic disorders than in the general population (Correll et al ., 2017), and are pre-determinants of more severe outcomes, such as cardiovascular disease. Indeed, as De Carlo et al note, cardiovascular disease is the main cause of death in people with schizophrenia (Crump et al ., 2013; Laursen et al ., 2014; Suetani et al ., 2021). There are a number of potential explanations for the comorbidity.…”
mentioning
confidence: 99%
“…In this issue, (De Carlo et al, 2023) have analysed the metabolic risk factors in 120 consecutive people being treated with long-acting injectable antipsychotic medications at a large outpatient department in Milano, Italy. Unsurprisingly, they found that about a third presented with metabolic syndrome, and over half showed evidence of abdominal obesity.…”
mentioning
confidence: 99%